Problems with plate tectonic models for Baffin Bay Nares Strait: evidence from the Labrador Sea - Grant, Alan C. (Meddelelser om Grønland. Geoscience, 1982)
Plate tectonic models for the geologic development of Baffin Bay require major strike-slip displacement through Nares Strait. However, these models are based mainly upon observations made in other areas, such as the Labrador Sea, the North Atlantic, or the Arctic Ocean. This paper reviews a synthesis of available geological and geophysical data from the Labrador Sea that indicate severe problems with plate tectonic models for that area, which must also affect any such model for Baffin Bay. The Labrador Sea data can be interpreted alternatively in terms of vertical crustal movements. Applied to Baffin Bay, such a mechanism involving vertical rather than lateral crustal displacements accommodates the evidence from field studies in the Nares Strait area that there is geological continuity from Ellesmere Island to Greenland.